STUDY OF GRINDED POWDER MORPHOLOGY AS FENTON CATALYST FOR DEGRADING DYE WASTE - Isti Hanifah, Azhar
A large number of textile industries in the watershed (DAS) pollute the environment with the presence of dye waste which is very difficult to degrade. Almost all dyes used in the textile industry are azo dyes. These compounds are carcinogenic and interfere with the transfer of oxygen in human blood. In order to prevent pollution that can threaten human life, it is necessary to have the right method to reduce or even eliminate water pollution. A promising method for degrading synthetic dyes waste is Advanced Oxidation Processes (AOPs). This method has the ability to produce hydroxyl radicals with high oxidation ability which can break down organic dyes into harmless compounds such as CO2 and H2O. Among the types of AOPs, the Fenton reaction has attracted a lot of attention because of its high degradability, easy processing, and economy. Currently, heterogeneous Fenton is being developed because it has a wider pH susceptibility compared to homogeneous Fenton, but there is still a need for development to optimize its workability above pH 4. In previous studies, it was known that heterogeneous Fenton originates from grinding waste in the form of core-shell has the ability to degrade dye waste. In this research, a further study was developed on the effect of the materials type of the grinding powder and its catalytic activity to degrade dye waste. The grinding powder were produced by Rema grinded machine type DS04/175, with a maximum speed of 2900 rpm. SEM-EDS results show that the harder steel, K100, has a high melting temperature produces irregular shapes morphology. While, the VCL140, St37 and AISI1018 steels with softer hardness has lower melting temperature, produces core-shell morphology. Core-shell morphology has better degradability of dye waste than irregular shapes morphology sample. In addition, increasing the concentration of fenton-like catalys and APS can also increase the catalytic activity of the degrading dye waste.